2016
DOI: 10.1007/s11250-016-1120-8
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus surveillance of cattle in Fiji, Papua New Guinea, Vanuatu, the Solomon Islands and a case for active disease surveillance as a training tool

Abstract: There have been no surveys of the cattle population for brucellosis in Pacific Island Countries and Territories (PICTs) for more than 15 years. This study used disease surveillance as a capacity building training tool and to examine some of the constraints that impede surveillance in PICTs. The study also developed and implemented a series of surveys for detecting antibodies to B. abortus in cattle in Fiji, Papua New Guinea, Vanuatu and the Solomon Islands contributing to OIE requirements. The findings indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Laboratory records from a study by revealed the presence of seropositive animals in four out of five districts in Maluku and one out of five districts in Papua, indicating the widespread nature of bovine Brucellosis in these areas (28). Additionally, emphasized the need for active disease surveillance in Papua New Guinea (PNG) and other Pacific Island Countries and Territories (PICTs) to address the re-emergence of Brucellosis, highlighting the significance of monitoring and control measures in these regions (41).…”
Section: Resultsmentioning
confidence: 99%
“…Laboratory records from a study by revealed the presence of seropositive animals in four out of five districts in Maluku and one out of five districts in Papua, indicating the widespread nature of bovine Brucellosis in these areas (28). Additionally, emphasized the need for active disease surveillance in Papua New Guinea (PNG) and other Pacific Island Countries and Territories (PICTs) to address the re-emergence of Brucellosis, highlighting the significance of monitoring and control measures in these regions (41).…”
Section: Resultsmentioning
confidence: 99%
“…A search for published articles on cattle diseases in the PICTs revealed limited information. Data from the few studies on dairy cattle showed that leptospirosis, brucellosis, tuberculosis, and helminths are the major dairy cattle diseases [36][37][38].…”
Section: Occurrence Of Infectious Cattle Diseases and Poor Husbandry ...mentioning
confidence: 99%
“…According to the 2020 agricultural census, there were 119,691 cattle, 37,435 sheep, 143,853 goats, and 1,412, 901 chicken (Ministry of Agriculture, 2020). Despite the importance of livestock, there has been limited studies on animal diseases with brucellosis, and bovine tuberculosis being the most studied (Tukana et al, 2016;Borja et al, 2018). Additionally, the prevalence of AMR in food animals in Fiji remain unknown (Magiri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%